SENI ISLAM TERAPI MURATTAL ALQURAN SEBAGAI PENDEKATAN KONSELING UNTUK MENGATASI KECEMASAN - Syafrianto Tambunan (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2018)
Every individual has experienced fear and anxiety in life. This is usually caused by excessive emotions, fear of the future, inner contradictions, or something that happens unexpectedly. Islamic counseling is considered to be able to overcome the spiritual emptiness that is often the cause of mental disorientation of modern humans. One method that can be implemented in the context of counseling therapy is murattal (chanting) the Qur’an. With descriptive and analytical approaches, namely narrating the characteristics of an object holistically and systematically, this article explains the steps of counseling therapy through Islamic art, which in this case is the murattal art of the Qur’an. This paper concludes that murattal of the Qur’an can be an alternative approach in the practice of Islamic counseling.